Agricultural policy under economic development - Heady, Earl O. (Iowa State University Press, 1962)
This book is intended mainly for students, professional economists and policy administrator. It was written to fill a void; namely, the lack of a book in policy which combines a fair amount of theory and analytical treatment with the more descriptive and literary analysis of agricultural structure and policy.